2007
DOI: 10.3354/meps329205
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of sea urchin Diadema antillarum populations is correlated to increased coral and reduced macroalgal cover

Abstract: We surveyed the benthic community structure and population density of the longspined sea urchin Diadema antillarum on the shallow fore-reefs of the Gandoca-Manzanillo Wildlife Refuge, Caribbean Costa Rica, in September and October 2004. In zones with high densities of D. antillarum (> 0.6 ind. m -2 ), the cover of non-calcareous macroalgae, known coral competitors, was low and that of live coral was high, whereas the opposite occurred in zones with low densities of D. antillarum (< 0.1 ind. m -2 ). D. ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 20 publications
6
39
0
Order By: Relevance
“…Carpenter and Edmunds (2006) reported similar observations from reefs elsewhere in the Caribbean (see also Chiappone et al 2001, Macintyre et al 2005, Weil et al 2005, Debrot and Nagelkerken 2006, Steiner and Williams 2006, Noriega et al 2006, Myhre and Acevedo-Gutiérrez 2007, Jordán-Garza et al 2008, Blanco et al 2010, Ruiz-Ramos et al 2011, Bodmer et al 2015.…”
Section: Tests Of the Hypothesessupporting
confidence: 54%
“…Carpenter and Edmunds (2006) reported similar observations from reefs elsewhere in the Caribbean (see also Chiappone et al 2001, Macintyre et al 2005, Weil et al 2005, Debrot and Nagelkerken 2006, Steiner and Williams 2006, Noriega et al 2006, Myhre and Acevedo-Gutiérrez 2007, Jordán-Garza et al 2008, Blanco et al 2010, Ruiz-Ramos et al 2011, Bodmer et al 2015.…”
Section: Tests Of the Hypothesessupporting
confidence: 54%
“…Diadema was also absent at reef slopes, except (Miller et al 2003) and earlier in Barbados (Hunte & Younglao 1988) indicated the possible beginning of a full population recovery in the Caribbean. Such a recovery has been recently documented in one site (0.01 ind./m 2 ), in Sabana-Camagüey Archipelago, north-central Cuba (Alcolado et al unpublished data), and absent at all sampled locations in Punta Francés, southwestern Cuba (Williams & Polunin 2001, Guardia et in Costa Rica (Alvarado et al 2004, Myhre & Acevedo-Gutiérrez 2007, Puerto Rico (Weil et al 2005) Barbados (Macintyre et al 2005, Carpenter & Edmunds 2006, Curaçao (Debrot & Nagelkerken 2006), Dominica (Steiner & Williams 2006), Jamaica, St. Croix, Grenada, Bonaire, Belize (Carpenter & Edmunds 2006), venezuela (Noriega et al 2006) and Yucatan (Jordán-Garza et al 2008).…”
Section: Discussionmentioning
confidence: 64%
“…Publications by Idjadi et al (2010) and Macintyre et al (2005) include photographs depicting the striking difference between the two areas. More juvenile coral colonies can be found in the Diadema zones (Carpenter & Edmunds 2006, Edmunds & Carpenter 2001, Furman & Heck 2009, Myhre & Acevedo-Gutierrez 2006. These colonies have higher survivorship and higher growth rates than colonies in algal zones (Idjadi et al 2010).…”
Section: Changes In Reef Communities In the Absence Of Diadema Antillmentioning
confidence: 98%